2011
DOI: 10.1063/1.3543840
|View full text |Cite
|
Sign up to set email alerts
|

Defect dynamics and spectral observation of twinning in single crystalline LaAlO3 under subbandgap excitation

Abstract: We have investigated the photoluminescence and ultrafast dynamics of LaAlO3 crystal. The photoluminescence consists of a broad spectrum and two sharp peaks, which arise from various defect levels within the bandgap. A doublet splitting of roughly 6 nm is seen in these two sharp peaks. An Al displacement of 0.09 Å in a sublattice, which is possible because of twinning, is adequate to explain the spectral splitting. Femtosecond pump probe experiments reveal further that many of these defect levels have a few pic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 22 publications
2
20
0
Order By: Relevance
“…This scenario of metallic junction transport as a result of the formation of a defect-related quasiconduction band is consistent with a recent report on metal/LAO/ Nb-STO heterostructures [68]. However, in the thick LAO films on the scale of 100 nm, the defect states exist at roughly 2 eV below the conduction-band edge [68,69], which was also proposed in a first-principles study [46]. In contract, in our Pt/LAO/STO heterostructure with an ultrathin LAO layer, the electronic band structure is modified in a different way by the oxygen vacancies.…”
Section: First-principles Calculationssupporting
confidence: 74%
“…This scenario of metallic junction transport as a result of the formation of a defect-related quasiconduction band is consistent with a recent report on metal/LAO/ Nb-STO heterostructures [68]. However, in the thick LAO films on the scale of 100 nm, the defect states exist at roughly 2 eV below the conduction-band edge [68,69], which was also proposed in a first-principles study [46]. In contract, in our Pt/LAO/STO heterostructure with an ultrathin LAO layer, the electronic band structure is modified in a different way by the oxygen vacancies.…”
Section: First-principles Calculationssupporting
confidence: 74%
“…Several recent reports of PL spectra in LaAlO 3 have shown the presence of various types of defects via sharp or broad peaks below the bandgap. Kawabe et al 27 show the presence of a broad PL at ~2.5 eV attributed to oxygen vacancies whereas Chen et al 18 show the presence of two narrow peaks at 1.7 and 1.8 eV and a broad peak at 2.1 eV arising from the displacement of cations from their regular sites. Theoretically, it has been shown that in LaAlO 3 Schottky-like defects that maintain charge neutrality are dominant under all conditions, besides oxygen vacancies and anti-site defects19.…”
Section: Discussionmentioning
confidence: 99%
“…This material is a promising gate insulator for advanced Metal-Oxide-Semiconductor (MOS) devices101112. However, it has been reported to possess localized mid-gap states due to various types of defects — interstitials, vacancies, anti-sites, impurities — causing leakage current and it is important to understand the various defects and their dynamics both experimentally and theoretically13141516171819. On the other hand, lattice strain plays an important role on the defects and their dynamics and hence on the related physical properties20.…”
mentioning
confidence: 99%
“…Rare earth based oxides, perovskites and their interfaces are of great interest in optical studies as rare earth ions can serve as emission centers for laser systems, such as Nd:YAG (Nd-doped Y 3 Al 5 O 12 )1617. The photoluminescence (PL) properties of the Nd 3+ ion in NGO single crystals were studied by Orera et al 18, where the samples were excited by light from a tungsten lamp.…”
mentioning
confidence: 99%